Incidence of Different Cytological Cell Types of Lung Cancer Diagnosed Under CT-guided FNAC in a Tertiary Care Hospital in Khulna (Mediscope, 2025)
Background: Lung cancer is the leading cause of cancer-related mortality worldwide, and its incidence is increasing in developing countries, including Bangladesh. CT-guided fine-needle aspiration cytology (FNAC) is a minimally invasive and reliable diagnostic modality for lung cancer diagnosis. This study aimed to investigate the incidence of different histopathological cell types of lung cancer diagnosed under CT-guided FNAC in a tertiary care hospital in Khulna.Methods: This is a hospital-based observational study carried out on 60 subjects in the Medicine Department of Gazi Medical College Hospital (GMCH), Khulna over 06 years, from March 2016 to March 2022 in collaboration with the Radiology and Imaging Department. A self-administered questionnaire containing different sets of questions regarding lung cancer was used for data collection. Detailed demographic data were collected from the patients and recorded in this study. Data were entered and analyzed using SPSS software.Results: The mean age of the patient was 53.72±9.78 years. The male and female ratio was 4:1. The commonest presentations were cough, weight loss, dyspnea, and chest pain (76.66%, 73.33%, 70.00%, and, 53.33% respectively). Smoking was a prime risk factor. Primary diagnosis of lung lesion was made by evaluation of history, and clinical examination and based on CXR finding and categorization was done based on FNAC under CT scan guide. Among the clinically suspicious lung cancer cases, 54 (90%) were diagnosed as bronchial carcinoma and the remaining 6 (10%) were non-specific infection. Non-small cell carcinoma was found to be the most prevalent in 42 patients (70%) according to CT-guided FNAC. The correlation of cytological examination with clinical and radiological findings revealed that cytological examination was more precise, and correlated with the suspected malignant lung cancer.Conclusion: CT-guided FNAC is a valuable and fairly accurate diagnostic aid for pulmonary mass lesions with a reasonable rate of complication in suspected cases. The Clinico-histopathological pattern of lung cancer has changed recently. The study emphasizes the early detection and diagnosis of lung cancer, particularly in high-risk populations such as smokers. The incidence of adenocarcinoma is increasing, and becoming the most common cause in both smokers and non-smokers.Mediscope 2025;12(1): 18-22